Organocatalysed one-pot three component synthesis of 3,3′-disubstituted oxindoles featuring an all-carbon quaternary center and [spiro 2H-pyran-3,4′-indoline] - Nichinde, Chandrakant B.; Patil, Baliram R.; Chaudhari, Suryakant S.; Mali, Bhupendra P.; Gonnade, Rajesh G.; Kinage, Anil K. (RSC Advances, 2023)
A simple and efficient methodology for the one-pot synthesis of 3,3 `-disubstituted oxindoles featuring an all-carbon quaternary center has been demonstrated through l-proline catalysed three-component reaction based on sequential Knoevenagel condensation/Michael addition and also one-pot synthesis of spiro[2H-pyran-3,4 `-indoline] through consecutive Knoevenagel condensation/Michael addition/reduction/cyclization reactions from readily available isatin derivatives, malononitrile, and ketones. The present methodology presents several advantages, including simple reaction set-up, short reaction times, and easy to work-up. Also, this strategy offers broad substrate scope with excellent yields and high atom economy, under mild reaction conditions.

Organocatalyzed [4+2] cycloaddition of α,β-unsaturated ketones and isatylidene malononitrile: accessing spiro[3-arylcyclohexanone]oxindole derivatives - Patil, Baliram R.; Nichinde, Chandrakant B.; Chaudhari, Suryakant S.; Krishna, Gamidi Rama; Kinage, Anil K. (RSC Advances, 2024)
Herein, we developed a series of compounds featuring spiro[3-arylcyclohexanone]oxindoles through Barbas [4 + 2] cycloaddition reactions between isatylidene malononitrile and alpha,beta-unsaturated ketones using l-proline as an organocatalyst. The reported methodology offers many advantages such as mild reaction conditions, diverse substrate scope with high yields, easy reaction setup, and use of easily synthesizable starting materials. An l-proline catalyzed-Barbas-[4 + 2]-cycloaddition reaction is reported for the synthesis of spiro[3-arylcyclohexanone]oxindole derivatives. The method can tolerate a diverse substrate scope with high yields.